ECONOMIC RECOVERY MECHANISMS IN WARTIME - Anatolii Mazaraki; Ganna Duginets (Agora International Journal of Economical Sciences (AIJES), 2023)
Restoring national competitiveness requires a lot of time, effort, and financial investment, and, in particular, involves a structural sectoral transformation, reorientation, and rethinking of target orientations and levers of the economy. Analysis and systematization of the experience gained by other countries that were in a situation similar to the unjustified russian invasion of Ukraine on February 24, 2022, working out ways to solve problems will become a road map for recovery after the victory and in the process of rebuilding the country. The purpose of the article is to determine the key economic recovery mechanisms in wartime on the study of similar recovery experience in world system. As a result of the study, the main drivers and levers of economic recovery are determined, which will help to restore the national economy step by step, and alternative methods are proposed, which are based on a combination of the experience of different countries.
Keywords: 330